Analisis Nomina Arkais dalam Bahasa Minangkabau Isolek Rao-Rao Kabupaten Tanah Datar - Wahyuni, Sri (Universitas Andalas, 2025)
This research aims to: 1) describe archaic nouns in Rao-rao isolect, Tanah Datar Regency; 2) describe nouns that are close to archaic in the Minangkabau language Rao-rao isolect, Tanah Datar Regency; and 3) explain the causes of archaism in Rao-rao isolect, Tanah Datar Regency. Data was obtained through direct interviews in the field. Data is provided by: (1) listening, (2) interviewing, and (3) recording. Data analysis was carried out using the intralingual matching method, with three basic techniques, namely the comparison of comparison technique (HBS), the technique of comparison of differences (HBB), and the technique of comparison of comparing main points (HBSP). Based on data analysis and classification, 61 archaic nouns were found, namely ande, abak, apak, alu, amban poruk, awe, bagua, buntiah, cibuak, cimporong, colok, dama, darehuk, dukua, iyek, kalang ulu, kampia, kapuran sada, karang pagi, karang tigo, kincia, codek, kombuk, kramopon, kula, kumbuak, loka, langkan, lantera, losuang, maniak, mansala, mansiang, oncu, palanta, pangalan, paraku, parian, ponai, pasu, punjin, pusuang, roban, saga, sanggan, salendang, sikiran, silukuk, singulu, sudu, sugi, sula, suluah, suluk, sumpik, strongkeng, tabuang kowa, tamingka, tangkelek, tangkuluak, and furnace; and 17 almost archaic nominations, namely amai, biliak, cupak, garembe, jamban, juada, katidiang, kawa, pinggan, polak, puntuang, rhizome, sanduak, sarowa, solang, umak and unggeh. There are two causes for the occurrence of noun archaism in Minangkabau language, namely changes in people's lifestyles and shifts in the use of vocabulary.